The Role of Macrophage Migration Inhibitory Factor in Adipose-Derived Stem Cells Under Hypoxia - Hofmann, Elena; Soppert, Josefin; Ruhl, Tim; Gousopoulos, Epameinondas; Gerra, Simona; Storti, Gabriele; Tian, Yuan; Brandhofer, Markus; Schweizer, Riccardo; Song, Seung-Yong; Lindenblatt, Nicole; Pallua, Norbert; et al. (Frontiers in Physiology, 2021)
Background: Adipose-derived stem cells (ASCs) are multipotent mesenchymal stem cells characterized by their strong regenerative potential and low oxygen consumption. Macrophage migration inhibitory factor (MIF) is a multifunctional chemokine-like cytokine that is involved in tissue hypoxia. MIF is not only a major immunomodulator but also is highly expressed in adipose tissue such as subcutaneous adipose tissue of chronic non-healing wounds. In the present study, we investigated the effect of hypoxia on MIF in ASCs isolated from healthy versus inflamed adipose tissue. Methods: Human ASCs were harvested from 17 patients (11 healthy adipose tissue samples, six specimens from chronic non-healing wounds). ASCs were treated in a hypoxia chamber at <1% oxygen. ASC viability, MIF secretion as well as expression levels of MIF, its receptor CD74, HIF-1α and activation of the AKT and ERK signaling pathways were analyzed. The effect of recombinant MIF on the viability of ASCs was determined. Finally, the effect of MIF on the viability and production capacity of ASCs to produce the inflammatory cytokines TNF, IL-6, and IL-1 was determined upon treatment with recombinant MIF and/or a blocking MIF antibody. Results: Hypoxic treatment inhibited proliferation of ASCs derived from healthy or chronic non-healing wounds. ASCs from healthy adipose tissue samples were characterized by a low degree of MIF secretion during hypoxic challenge. In contrast, in ASCs from adipose tissue samples of chronic non-healing wounds, secretion and expression of MIF and CD74 expression were significantly elevated under hypoxia. This was accompanied by enhanced ERK signaling, while AKT signaling was not altered. Recombinant MIF did stimulate HIF-1α expression under hypoxia as well as AKT and ERK phosphorylation, while no effect on ASC viability was observed. Recombinant MIF significantly reduced the secretion of IL-1β under hypoxia and normoxia, and neutralizing MIF-antibodies diminished TNF-α and IL-1β release in hypoxic ASCs. Conclusions: Collectively, MIF did not affect the viability of ASCs from neither healthy donor site nor chronic wounds. Our results, however, suggest that MIF has an impact on the wound environment by modulating inflammatory factors such as IL-1β.